Revolusi Branding di Dunia Metaverse Modern - Sandy Gunarso (Lembaga Riset dan Pengabdian Masyarakat Institut Bisnis Nusantara, 2025)
This study analyzes the transformation of branding strategies in line with the development of the metaverse as an integrated immersive digital ecosystem. The discussion focuses on the reconfiguration of the relationship between brands and audiences when interactions take place in three-dimensional spaces, are grounded in virtual identities, and are supported by decentralized platforms. In this context, the metaverse is understood as an environment that enables dynamic engagement, multisensory narrative flows, and persistent worlds that position brands as symbolic systems continuously negotiated through user participation. The study highlights a shift from visually oriented, one-way branding toward a paradigm of experience, participation, and co-creation, in which audiences play a greater role in the production and legitimation of brand meaning. At the same time, the research identifies critical issues such as data governance and ethics, technological infrastructure readiness, and organizational capabilities in managing change. Overall, the findings indicate the need to renew branding strategy frameworks so that brands remain relevant and competitive within an evolving virtual landscape. Penelitian ini menganalisis transformasi strategi penjenamaan seiring berkembangnya metaverse sebagai ekosistem digital imersif yang terintegrasi. Fokus pembahasan diarahkan pada konfigurasi ulang relasi antara merek dan audiens ketika interaksi berlangsung dalam ruang tiga dimensi, berbasis identitas virtual, dan ditopang oleh platform terdesentralisasi. Dalam konteks tersebut, metaverse dipahami sebagai lingkungan yang memungkinkan keterlibatan dinamis, alur naratif multisensori, serta dunia persisten yang menjadikan merek sebagai sistem simbolik yang terus dinegosiasikan melalui partisipasi pengguna. Kajian ini menyoroti pergeseran dari penjenamaan yang berorientasi pada tampilan visual dan komunikasi satu arah menuju paradigma pengalaman, partisipasi, dan ko-kreasi, sehingga audiens memiliki peran lebih besar dalam produksi dan legitimasi makna merek. Di saat yang sama, penelitian mengidentifikasi isu-isu kritis seperti tata kelola dan etika data, kesiapan infrastruktur teknologi, serta kapabilitas organisasi dalam mengelola perubahan. Secara keseluruhan, temuan penelitian mengindikasikan perlunya pembaruan kerangka strategi penjenamaan agar merek tetap relevan dan kompetitif dalam lanskap virtual yang terus berkembang